Pengembangan Awal Skala Keyakinan Teori Konspirasi Cina di Indonesia - Suwanda Priyadi; Audi Ahmad Rikardi (Jurnal Ilmiah Psikologi Candrajiwa, 2025)
The Chinese-Indonesian ethnic group is one of the minority communities in Indonesia that frequently faces negative attitudes from other ethnic groups. One possible explanation for this phenomenon is the belief in conspiracy theories. Therefore, the aim of this study was to develop and validate the Belief in Chinese Conspiracy Theory Scale in the Indonesian context. A total of 117 university students participated in this study, with 77.7% identifying as female. Exploratory factor analysis revealed that the 27 items measuring belief in conspiracies involving China formed three main factors: Factor 1 (economic involvement, seven items), Factor 2 (Covid-19 involvement, four items), and Factor 3 (political involvement, four items). Internal consistency reliability analysis showed Cronbach’s alpha values of 0.850, 0.826, and 0.707 for each respective factor. Further confirmatory factor analysis and validation using additional sources of evidence are recommended to support the interpretation of scores on the Belief in Chinese Conspiracy Theory Scale.